PENGARUH PREFERENSI DAN MINAT TERHADAP KEPUTUSAN MILENIAL DALAM KREDIT PEMILIKAN RUMAH DI BJB TAMANSARI BANDUNG - Nurrunnajmi, Tirahaifa; Amaliah, Ima (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
Nowadays, house prices are increasingly soaring, which impacts the Millennial generation's ability to buy a house. The millennial generation will find it difficult to own a home because the increasingly expensive house prices do not match the income earned. This study aims to understand the influence of preferences and intention on millennial purchasing decisions in home ownership loans at BJB Tamansari Bandung. The method used is descriptive quantitative. In this study, researchers gave questionnaires to 100 respondents of BJB Tamansari Bandung millennial customers and processed them using the Smart PLS-SEM 3.0 application. The results showed that preferences and intentions partially influenced millennial decisions in home ownership loans at BJB Tamansari Bandung. In comparison, intention does not directly affect millennial customer preferences in mortgage loans. The reason is the economic factors faced by millennial groups. Property market conditions, lifestyle, education level, and job mobility influence interest in buying a mortgage.